Improved cooking stoves that end up in smoke? - Michael Grimm; Jörg Peters (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2012)
More than 2.7 billion people in developing countries rely on biomass for cooking with profound implications for their well-being. Two million people die every year due to cooking related smoke emissions - more than are killed by malaria. In recent years, an international movement has gained momentum on the level of the United Nations that intends to combat this plight by the dissemination of improved cooking stoves. A recent study conducted by Hanna, Duflo and Greenstone based on a field experiment in India has attracted much attention, also in the popular press. It does not confirm the optimistic results on the impacts of improved cooking stoves that hitherto can be found in the literature. Editorial notes in newspapers like the New York Times took up findings from the study and vehemently criticized the international efforts to improve access to cleaner cooking fuels as ineffective. The present RWI Positionen policy paper argues that this journalistic verdict is premature and that the results of the study are overstressed. While the study is in principle a meaningful contribution to the improved stoves literature, its findings are very specific to the local environment in which it was conducted and as we argue the insights can barely be transferred to other areas in the developing world.
Keywords: 330; Herd; Brennholz; Entwicklungshilfe; Indien; Entwicklungsländer